RADIO KOMUNITAS SEBAGAI MEDIA ALTERNATIF UNTUK PEMBERDAYAAN MASYARAKAT - Husni Mubaroq; Ega Fitri Qur’aini (JISOS: JURNAL ILMU SOSIAL, 2023)
The purpose of this study is to describe the role of community radio as an alternative medium for empowering local communities. The principle of community media is "by the community, for the community, and for the community". The main goal is to build community and local capacity to help improve the lives of local people. This study used descriptive qualitative method. Based on the results of the study, the use of community radio has not maximized the enthusiasm of the local people themselves who still do not know how to use local media. There is a reflection of the active role of the monitoring group (active listeners) in the routine work of community radio. Only community radio is actively supported by monitoring groups that can play a role of power to community members. Actively maintaining and exploring broadcast work routines for opportunities and problems for community members and looking for solutions to problems faced by community members